2014
DOI: 10.1186/2193-1801-3-103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience of children with disabilities at school settings in Vietnam context

Abstract: The initial findings from 230 questionnaires' survey and 36 interviews, in which informants are CWD, children with non-disabilities (CWND), parents of CWD, and teachers in school settings, are stated as: (a) the general understanding of disability is based on medical model and individual model rather than social model, such understandings contribute great impacts to the CWD's experiences in their daily life in general and in school contexts in particular; (b) the most important difficulties which CWD experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…In which children with dissabilities are able to attend, to make their voice and to contribute to. School setting is the most significant one for children with dissabilities to make any changes on their social awareness and on accessing the sustain-able inclusion process [14].…”
Section: Results and Discusionmentioning
confidence: 99%
“…In which children with dissabilities are able to attend, to make their voice and to contribute to. School setting is the most significant one for children with dissabilities to make any changes on their social awareness and on accessing the sustain-able inclusion process [14].…”
Section: Results and Discusionmentioning
confidence: 99%
“…In this connection, the Asian Development Bank (2014) states that the vocational training providers in Nepal are mostly under resourced and insufficiently disability-friendly although the short-term skills training for disadvantaged groups such as PWDs is expanding in the country. The insufficient accessibility of learning environment, as described by the participants, has illuminated a gap in the inclusion of learners with disabilities in the vocational training sector (Tran, 2014). Inclusion is about a person's right to belong to her/his local mainstream educational institution, to be valued for who s/he is and to be provided with all the support s/he needs to thrive (Rieser, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the experience of children with disabilities (CWDs) in school settings in the context of Vietnam revealed that the CWDs' most important difficulties were related to learning facilities, empathy from their peers and barriers caused by the physical environment (Tran, 2014). The study showed that most of the respondents' understanding of disability was based on the medical and individual model.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…De hecho, el área con menor desarrollo es accesibilidad y diseño universal, ya que cerca de un 60 % señala que el mobiliario no contaría con adaptaciones al puesto de trabajo del estudiante en situación de discapacidad. Esto es preocupante en la medida en que las dificultades más importantes en la experiencia que presentan los niños con discapacidad en la escuela, están en las instalaciones de aprendizaje, la empatía de sus pares y los obstáculos en el entorno físico para los estudiantes (Tran, 2014).…”
Section: Discussionunclassified